Digital Marketing on Young Consumer Behavior: Systematic Literature Review - Stefani Dewinatalia; Irwansyah Irwansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Young people continue to be the target of digital marketing. This systematic literature review aims to identify the stages of consumer behavior from young people's behavior towards digital marketing. This systematic review of the literature seeks to understand to what extent and at what stage in relation to the consumer behavior experienced by young consumers towards digital marketing. The methodology of this study involves a systematic review of empirical studies published from 2018 to 2022 and identifies stages of consumer behavior experienced by young people. Lavidge and Steiner's (1961) model was used to measure the influence of digital marketing on various stages of consumer behavior such as awareness, interest, belief, purchase, and post-purchase behavior. The review begins with a study that includes and follows the structure of PRISMA, which consists of study identification, screening and evaluation, study analysis and synthesis, and final study conclusions. In general, research shows that young people experience awareness, interest, belief, and purchase towards digital marketing. The findings from the qualitative study are summarized and these findings provide insight into how digital marketing influences the behavior of young people.